efecto de la reduccion del area foliar sobre la produccion de Pimiento (Capsicum annuum L.) - Muro, J.=700 1 Lamsfus, C.; Fernandez Militino, A.
(Es, En)
ilus., 9 ref.
Keywords: DEFOLIACION; SIMULACION; SUPERFICIE FOLIAR; CAPSICUM ANNUUM; ESPAÑA; PEDRISCO